New Pergalumna (Acari, Oribatida, Galumnidae) from Peru - Ermilov, Sergey G.; Friedrich, Stefan (Zootaxa, 2016)
Six species of oribatid mites of the genus Pergalumna (Oribatida, Galumnidae) are collected from the German Expedition to Amazonian Peru in 2013; of these, three are new for science, described from upper soil and leaf litter in the primary evergreen lowland rainforest. Pergalumna (Pergalumna) parapassimpunctata sp. nov. is morphologically most similar to P. (P.) passimpunctata Balogh & Mahunka, 1969, but differs from the latter by the presence of foveolate body surface, two pairs of porose areas Aa and minute interlamellar setae, and the absence of porose areas A3. Pergalumna (Pergalumna) krisperi sp. nov. is morphologically most similar to P. (P.) cardosensis Pérez-Íñigo & Baggio, 1986, but differs from the latter by the smaller body size, rostral and lamellar setae of medium size and the presence of four pairs of notogastral porose areas. Pergalumna (Pergalumna) lenticulata sp. nov. is morphologically most similar to P. (P.) decorata Balogh & Mahunka, 1977, but differs from the latter by the larger body size and the presence of lenticulus and bidentate rostrum. The species Pergalumna (Pergalumna) bryani Jacot, 1934 is recorded for the first time in Peru.